Long-term loading and regional bone mass of the arm in female volleyball players - Alfredson, H.; Nordstrom, P.; Pietila, T.; Lorentzon, R. (Calcified Tissue International, 1998)
In the present study, we compared the bone mineral content (BMC) and bone mineral density (BMD) in the arms of 11 female volleyball players (mean age 22.0 +/- 2.6 years) training for about 8 hours/week, and 11 nonactive females aged 24.6 +/- 3.1 years (mean +/- SD) not participating in regular or organized sport activity. Using dual X-ray absorptiometry (DXA), BMC was measured in the proximal and distal humerus, and BMD in the distal radius. Isokinetic concentric peak torque (highest value attained during 5 or 10 repetitions) of the rotator muscles of the shoulder and flexor and extensor muscles of the elbow were measured using an isokinetic dynamometer. The volleyball players had significantly higher BMC (P < 0.05) at the proximal humerus of the dominant arm compared with the nonactive group, but there were no differences between the groups in BMC of the distal humerus and BMD of the distal radius. In the volleyball players, BMC was significantly higher at the proximal humerus, at the distal humerus, and at the distal radius in the dominant compared with the nondominant arm. In the nonactive group, there were no significant differences in BMC and BMD between the dominant and nondominant arm at any site measured. Except for shoulder internal rotation strength and elbow flexion strength at 90 degrees/second that was higher in the dominant arm in the volleyball players, there were no significant differences in muscle strength of the rotator muscles of the shoulder and flexor and extensor muscles of the elbow between the dominant and nondominant arm in the volleyball players and nonactive controls. In the volleyball players, but not in the nonactive controls, there were several significant relationships between shoulder and elbow strength and BMC at the distal humerus of the dominant and especially the nondominant arm. These results show that young female volleyball players have a higher bone mass in the proximal humerus, distal humerus, and distal radius in the dominant compared with the nondominant arm, and a higher bone mass in the proximal humerus compared with nonactive controls. Muscle strength of the rotator muscles of the shoulder is not related to the higher bone mass in the proximal humerus of the dominant arm. Theoretically, the observed differences in bone mass can be related to the type of loading the skeleton undergoes when playing volleyball.